2008
DOI: 10.1243/09596518jsce490
|View full text |Cite
|
Sign up to set email alerts
|

Extensions of adaptive slope-seeking for active flow control

Abstract: To speed up gradient estimation in a slope-seeking controller two different modifications are proposed in this study. In a first approach, the gradient estimation is based on a locally identified black-box model. A further improvement is obtained by applying an extended Kalman filter to estimate the local gradient of an input-output map. Moreover, a simple method is outlined to adapt the search radius in the classical extremum-and slopeseeking approach to reduce the perturbations near the optimal state. To sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 32 publications
(60 reference statements)
0
21
0
Order By: Relevance
“…While some flow control methods such as extremum seeking (Henning et al 2008) and machine learning control (Gautier et al 2015) are model free, many more rely on having a mathematical model, and often a linear model, of the fluid system. For example, black-box linear models have often been used for convectively unstable flows such as the backward-facing step (Barbagallo et Modelling and feedback control of bistability in a turbulent bluff body wake 729 flows behave like a linear amplifier, thus allowing linear models to be obtained for various input-output behaviours.…”
Section: R D Brackston and Othersmentioning
confidence: 99%
“…While some flow control methods such as extremum seeking (Henning et al 2008) and machine learning control (Gautier et al 2015) are model free, many more rely on having a mathematical model, and often a linear model, of the fluid system. For example, black-box linear models have often been used for convectively unstable flows such as the backward-facing step (Barbagallo et Modelling and feedback control of bistability in a turbulent bluff body wake 729 flows behave like a linear amplifier, thus allowing linear models to be obtained for various input-output behaviours.…”
Section: R D Brackston and Othersmentioning
confidence: 99%
“…In particular, the adaptation time is found to be similar to, but slightly greater than, that of the system of Henning et al (2008) and Pastoor et al (2008). In general, for a given noise level from the plant (w of Fig.…”
Section: Single Variable Implementationsmentioning
confidence: 65%
“…2.1). Alternative gradient estimation methods have also been suggested by Henning et al (2008) who used an extended Kalman filter, finding it to be much faster than the estimation of the standard algorithm. This algorithm was also tested by Wu et al (2015) who confirmed this result.…”
Section: Introductionmentioning
confidence: 99%
“…As the closed-loop bandwidth using an ESC is very low, methods to increase it are listed in [12]. In [13], we proposed using an Extended Kalman Filter to significantly speed up the single input case. An extension to the multiple input case can be found in [14].…”
Section: Introductionmentioning
confidence: 99%